1996
DOI: 10.1007/bf01291789
|View full text |Cite
|
Sign up to set email alerts
|

Glial cell line-derived neurotrophic factor (GDNF) gene expression in the human brain: A post mortem in situ hybridization study with special reference to Parkinson's disease

Abstract: Glial cell line-derived neurotrophic factor (GDNF) is a potent neurotrophic factor for dopaminergic neurons. Since dopaminergic neurons degenerate in Parkinson's disease, this factor is a potential therapeutical tool that may save dopaminergic neurons during the pathological process. Moreover, a reduced GDNF expression may be involved in the pathophysiology of the disease. In this study, we tested whether altered GDNF production may participate in the mechanism of cell death in this disease. GDNF gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…29 GDNF may be involved in the etiology of neuropsychological disorders, such as mood disorders. [30][31][32] In our study, serum GDNF was increased by treatment with EA or fluoxetine. Furthermore, we found a strong correlation between the HDRS score and serum GDNF level in patients receiving EA treatment.…”
supporting
confidence: 53%
“…29 GDNF may be involved in the etiology of neuropsychological disorders, such as mood disorders. [30][31][32] In our study, serum GDNF was increased by treatment with EA or fluoxetine. Furthermore, we found a strong correlation between the HDRS score and serum GDNF level in patients receiving EA treatment.…”
supporting
confidence: 53%
“…This finding is supported by previous studies in which the most striking difference in patients suffering from PD was found in FGF-2 expression: a profound depletion of FGF-2 [from 82% (control brains) down to 12.7% (PD brains)] in the remaining DA neurons was found (Tooyama et al, 1994), whereas BDNF was only reduced from 65 to 43% (Parain et al, 1999). In situ hybridization failed to show any detectable levels of GDNF in PD or in control cases, suggesting that GDNF is not a major physiological factor during adulthood (Hunot et al, 1996). These postmortem studies are in good correlation with the present null mutant studies.…”
Section: The Snpc and Its Trophic Factorsmentioning
confidence: 94%
“…Concerning glial cell line-derived neurotrophic factor (GDNF), postmortem studies investigating its distribution in the human parkinsonian brain have yielded conflicting results (Hunot et al, 1996;Chauhan et al, 2001;Mogi et al, 2001). Since GDNF expression is reduced in the adult brain, the use of techniques that enhance the detection of low copy mRNA transcripts may be crucial for accurate quantification of its expression.…”
Section: Introduction: the Relevance Of Studying The Endogenous Gdnf mentioning
confidence: 99%
“…Post-mortem studies investigating GDNF distribution in the human parkinsonian brain have yielded conflicting results. In situ hybridization studies failed to detect GDNF mRNA in the human midbrain (Hunot et al, 1996), and no significant differences were found in GDNF content in the caudate-putamen and substantia nigra between PD and control samples (Mogi et al, 2001). Since the levels of other growth factors are decreased in PD brains, it was suggested that the unchanged levels of GDNF in PD might be due to compensatory production by glial cells (Mogi et al, 2001).…”
Section: Gdnf Expression Upon Nigrostriatal Injury: Role Of Neuronglimentioning
confidence: 99%